Getting to the top of mind: How reminders increase saving - Dean Karlan; Margaret McConnell; Sendhil Mullainathan; Jonathan Zinman (Yale University, Economic Growth Center, 2010)
We develop and test a simple model of limited attention in intertemporal choice. The model posits that individuals fully attend to consumption in all periods but fail to attend to some future lumpy expenditure opportunities. This asymmetry generates some predictions that overlap with models of present-bias. Our model also generates the unique predictions that reminders may increase saving, and that reminders will be more effective when they increase the salience of a specific expenditure. We find support for these predictions in three field experiments that randomly assign reminders to new savings account holders.
Keywords: D91; E21; 330; intertemporal consumer choice; savings; attention